Redescription of Centropages ponticus Karavaev, 1895 (Copepoda: Calanoida) from the Black Sea. - Prusova, I.Y., E.A. Galagovets & E.V. Popova (Arthropoda Selecta, 2019)
Centropages ponticus Karavaev, 1895 is an endemic to the Mediterranean basin and one of the common species of copepods in the coastal waters of the region. However, its first description is very short and incomplete, and as a consequence, some uncertainty in the issue of correct identification of this species still remains. In the present work, a complete illustrated description of C. ponticus from the Sevastopol Bay (Black Sea), a type locality of this species, is performed. Based on a comparative analysis of five species of the hamatus group of the genus Centropages including C. ponticus, a differential diagnosis of the latter is given. Differences in the morphological structure of C. ponticus from the Black (own data) and Mediterranean (literature data) seas are described. How to cite this article: Prusova I.Yu., Galagovets E.A., Popova E.V. 2019. Redescription of Centropages ponticus Karavaev, 1895 (Copepoda: Calanoida) from the Black Sea // Arthropoda Selecta. Vol.28. No.4. P.515–528. doi: 10.15298/arthsel. 28.4.04